Translation Strategies in the Localization of Instagram, X, and YouTube User Interfaces - Dea Yuanita Nasution; Halim, Suwarni Wijaya; Belinda Febrianty (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The difference between a common translation and user interface localization for a technology product has raised big questions regarding the implementation of its translation strategy. This research attempts to answer this inquiry by analyzing the tendency of translation strategies used in the localization process for social media Instagram, X (formerly known as Twitter), and Youtube from English to Indonesian. The method used in this translation is qualitative descriptive, focusing on the text elements in the user interfaces from all three social media. The data were collected through a direct exploration of all three social media user interfaces in both English and Indonesian versions. The data from this research are in the form of words, phrases, clauses, and sentences presented in each user interface. From the data analysis, it is concluded that the most dominant translation procedure in the localization process of all three social media is naturalization. Meanwhile, the method and ideology applied are semantic translation and foreignization. This finding provides insight into the importance of translation strategies in localization for social media applications and how this process affects Indonesian users' experience. The results of this research also provide that every localization process does not have to be dominated by a domestic translation strategy as the name suggests. In fact, most technology product localization is translated with a foreignization approach to maintain consistency across platforms.